Simultaneous cardio-cerebral embolization. A prospective study. (25th November 2020) - Mione, V; Leclercq, T; Bejot, Y; Lenfant, M; Maza, M; Zeller, M; Cochet, A; Cottin, Y
Abstract: Background: Atrial Fibrillation (AF) is a common cause of ischemic stroke but also the most common cause of Coronary Artery Embolism (CE). Many previous case of coexistence of coronary and cerebral embolism have been reported in the literature but in specific situations were clinical signs of stroke but also indisputable clinical and/or electrocardiographic (ECG) signs leaded to the realization of coronarography in emergency. Objectives: The aim of the study was to determine the existence of simultaneous cardio-cerebral embolization associated in patients with ischemic embolic stroke on de novo AF, in the absence of clinical and/or ECG signs evocative of myocardial infarction (MI). Methods: We prospectively included patients hospitalized in our institution for ischemic embolic stroke on de novo AF. Patients with history of ischemic disease were excluded. All patients had: 1/ troponin assay; 2/ Cardiac Magnetic Resonance (CMR) imaging with Late-Gadolinium Enhancement (LGE) in order to detect myocardial infarction; 3/ coronary exploration by cardiac CT scan or coronarography to exclude patients with significant coronary lesion. Results: Between January and December 2019, 32 patients were included. Of them, 15 had subendocardial or transmural LGE on CMR, evocative of MI. Among these 15 MIs we classified acute MIs according to the level of troponin at the admission in stroke unit, the coronarography and T2 hypersignal on cardiac MRI. Median delay of cardiac MRI was 6 days for acute MIs. CE was clearly identified by coronarography for 4 patients with acute simultaneous cardio-cerebral infarction (56%). The MRI abnormalities showed that lesions of all MIs were transmural, relatively small (average 1.3±0.44 segments) and in most cases in the inferior cardiac wall (47%) and these abnormalities were comparable in sequelae and acute MI. Moreover, the left appendage morphology was a "cactus" in 62.7% of simultaneous acute cardio-cerebral infarction and only 33% in patients without MI or sequelae MI. Strokes were mainly localized in the superficial territory of the middle cerebral artery, and were similar in patients with or without MI. In addition, the rate of sequelae strokes was higher in isolated stroke group than "cardiocerebral infarction" (29.5% versus 13.3%). Conclusion: Simultaneous acute cardio-cerebral infarction is not uncommon, diagnosed in 22% of our prospective cohort of embolic stroke. Cardiac MRI may help us to diagnose a concomitant cardiac embolization and evaluate the prognosis. Unfortunately optimal therapeutic strategy of these patients is still unknown. Funding Acknowledgement: Type of funding source: None